An examination of the impact of the historical cultural contact between the Kalanga and San groups in Western Zimbabwe since the pre-colonial period: the case of Bulilima - Ncube, Sizo Mandisi (Midlands State University, 2018)
The dissertation is mainly focused on the effects of cultural contact between the San and the Kalanga in Western Zimbabwe, Bulilima area from pre-colonial. The San solely survived on the environment, their religion was defined by the environment this has been evidenced by the supernatural phenomena and myths which were grounded on the environment. Before the advent of the Bantu speaking groups, the San were nomadic in nature, non-pastoralists, hence the study reflected on how the Bantu speaking groups turned the San into labourers. The research further highlighted on the origins of the Kalanga people who became the masters of the San on the San areas. The reasons why the San were not able to resist the Kalanga domination were simple based on the lack of leadership structures hence they were loosely united. The study concluded that there was no cultural diffusion but there was cultural hybridity because both the San and the Kalanga borrowed from each others’ culture however, it was noted that the San were affected the most as they were subjects of the Kalanga thus it was forced on them. The dissertation further highlighted on the effects of colonialism to both the San and the Kalanga people. The San were affected by colonial legislative policies which were meant to turn the Africans into colonial labour force. The San were mainly affected by the NLHA which entailed on the confiscation of land hence the San nomadic nature was dealt a blow, as it was regarded as vagrancy. Moreover, the GFPA criminalized San hunting activities hence the San were forced to rely on both the Kalanga and the Ndebele, the colonialists viewed the San hunting as poaching though it was not harmful to the environment because they hunted down sick animals.